Evaluating Ninth Graders’ EFL Textbook in the Ethiopian EFL Context: Vocabulary and Grammar in Focus - Addisu Sewbihon Getie (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
ABSTRACTThis study was conducted to evaluate the ninth graders’ EFL textbook in the Ethiopian EFL context from the perspective of Lexical Approach. To examine whether the principles of Lexical Approach designed by Lewis (1993, 2000, and 2008) were applied in the textbook, its vocabulary and grammar sections were critically evaluated, and to assess the teachability of the two skills in line with the contemporary literature on the lexical theory, the researcher selected vocabulary and grammar items from the entire textbook. The researcher included grade nine EFL teachers as participants because of their extensive EFL teaching experience at this level. The research data were collected employing documents and interviews as instruments and were analyzed quantitatively and qualitatively. Findings of this study show that vocabulary and grammar skills are not presented lexically in this EFL textbook. In addition, these skills are neither presented in unison in the textbook nor are treated non-dichotomously. Overall, this study's findings indicate that the EFL textbook under study is not suitable for teaching vocabulary and grammar lexically. The researcher, therefore, recommends that extensive research be conducted to explore the impacts of the Lexical Approach on learners' competence of English as a foreign language in this EFL context. ABSTRAKPenelitian ini dilakukan untuk mengevaluasi buku teks EFL siswa kelas sembilan dari perspektif Pendekatan Leksikal. Untuk menguji apakah prinsip-prinsip Pendekatan Leksikal yang dirancang oleh Lewis (1993, 2000, dan 2008) diterapkan dalam buku teks EFL dalam konteks sistem pendidikan Ethiopia, aspek-aspek kosakata dan tata bahasa dari buku teks tersebut dievaluasi secara kritis. Untuk menilai kemampuan mengajar dua keterampilan tersebut apakah sejalan dengan literatur kontemporer tentang teori leksikal, peneliti memilih aspek kosakata dan tata bahasa dari buku teks tersebut. Peneliti memasukkan guru EFL kelas sembilan sebagai responden studi karena mereka telah mengajar siswa EFL di kelas ini selama beberapa tahun. Data penelitian ini dikumpulkan dengan dokumen dan wawancara dan dianalisis secara kuantitatif dan kualitatif. Temuan penelitian ini menunjukkan bahwa kosakata dan keterampilan tata bahasa tidak disajikan secara leksikal dalam buku teks EFL siswa kelas sembilan. Selain itu, keterampilan ini juga tidak disajikan secara serempak dalam buku teks atau diperlakukan secara non-dikotomis. Secara keseluruhan, temuan penelitian ini menunjukkan bahwa buku teks dalam konteks EFL ini tidak sesuai untuk mengajarkan kosakata dan tata bahasa secara leksikal. Peneliti merekomendasikan agar dilakukan penelitian ekstensif untuk mengeksplorasi dampak Pendekatan Leksikal dalam mengembangkan semua aspek kompetensi bahasa Inggris sebagai Bahasa Asing peserta didik dalam konteks EFL ini. How to Cite: Getie, A. S. (2020). Evaluating Ninth Graders’ EFL Textbook in the Ethiopian EFL Context: Vocabulary and Grammar in Focus. IJEE (Indonesian Journal of English Education), 7(1), 1-21. doi:10.15408/ijee.v7i1.15738